GODS AND HEROES OF THE GREEKS - Rose, H. J. (Herbert Jennings), 1883-1961. Link ([S.l.])
1 online resource
Keywords: Gods and Heroes of the Greeks (1957) looks at the chief stories of Ancient Greece and how they influenced European literature for centuries. It accounts the later development of these stories, in and out of the Greek world.